Horizontal equity and the taxation of employed and self-employed workers - Freedman, J; Chamberlain, E (2014)
The schedular system of income tax in the UK frequently comes under attack, not least in relation to the distinctions it draws between the tax treatment of the employed and the self-employed. However, on examination, it appears that non-schedular systems of taxation share both these distinctions and the difficulties that arise from them, albeit to varying degrees. The division between employed and self-employed is also problematic for social security systems. These difficulties are found, to a greater or lesser extent, in all the jurisdictions studied by the authors. It may be argued that all or some of the tax and social security differences are justified by fundamental economic and legal differences between the nature of employment and selfemployment relationships. This may be true where the relationships compared are unambiguously, on the one hand, employment and, on the other, self-employment. However, there have always been non-standard relationships that combine characteristics of both these broad categories. This grey area appears to be increasing with changing work patterns. Consequently,the simple dichotomous system adopted by the UK tax and social security systems has come under pressure. This article considers the problems arising from this situation and some of the ideas that have been put forward to deal with them.